KAJIAN TEORITIS KEMAMPUAN CAPPING KATEKIN, KATEKU TANAT DAN QUARSETIN TERHADAP NANOPARTIKEL PERAK DENGAN MENGGUNAKAN METODA DFT-B - Arief, Syukri; -, Emriadi; Saputra, Ade (Jurnal Riset Kimia, 2015)
Interdiffusion mechanism of catechin, catechutannic acid and quercetin are studied by using DFT-B method. But before conducting these experiment, we perform molecular dynamic simulations to find adsorption models probability of each compound. Two models adsorption of quarcetin, four models for catechin and three models for catechutannic acid have been obtained from molecular dynamic simulations. Quantum parameter of each compound, energy and properties adsorption models have been calculated and discussed. The theoretical results were found to be consistent with the experimental data reported. Futhermore, optimization adsorption model samples show that all of adsorbents have weak bonds on the surface of silver nanoparticles. The mechanism can be classified as strong physisorption, so that catechin, catechutannic acid and quercetin can be categorized as good capping agent in synthesis of silver nanoparticles.